Public Diplomacy as an Instrument of International Politics in the Digital Era - Yusran, Yusran (International Journal of Demos (IJD), 2025)
Abstract This study aims to analyze the role of public diplomacy as an instrument of international politics in the digital era. The development of information and communication technology has revolutionized the way countries interact and influence global public opinion. Through a qualitative descriptive approach, this study examines how public diplomacy is utilized to build a positive image of the country, promote national interests, and strengthen relations between countries through various digital platforms, such as social media, news portals, and online campaigns. The results of the study show that public diplomacy as an instrument of international politics in the digital era has developed rapidly through the use of communication technology and social media that allows for more direct, fast, and broad interaction with the global community. The findings show that various strategies such as digital diplomacy through social media campaigns, cultural diplomacy in digital format through online festivals and exhibitions, educational diplomacy with online learning platforms and international research collaborations, to mass media diplomacy through positive and educational news have succeeded in improving a country's image, expanding international cooperation networks, and strengthening the country's position in the global arena. This study also reveals that the adaptation of public diplomacy to digital transformation is an important factor in achieving foreign policy goals and building more constructive and mutually beneficial international relations. Keywords: Public Diplomacy, International Politics, Digital Era, State Image, Digital Media